1999
DOI: 10.1037/0893-3200.13.2.209
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between parental anger and behavior problems in children and adolescents.

Abstract: Two studies examined the relationship between parental trait anger, parental symptomatology, and children's and adolescents' emotional/behavioral problems. Results of Study 1 suggested that parental trait anger did not serve as a mediator between parental symptoms and children's emotional/behavioral problems. Study 2, however, suggested that parental trait anger did serve as a mediator between parental depression and adolescents' emotional/behavioral problems. For internalizing behaviors, inward anger expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 39 publications
2
32
0
Order By: Relevance
“…For example, extensive research from both large longitudinal samples and clinical samples demonstrates links between maternal age at first birth and a diagnosis of conduct disorder, drug use, and gang membership among offspring (Nagin et al 1997;Pogarsky et al 2006;Wakschlag et al 2000). Similarly, a recent study demonstrated relatively consistent concurrent relations between maternal ratings of their trait anger and outward expression of anger and child and adolescent externalizing problems, particularly among boys (Renk et al 1999). Also, in a longitudinal study of low income children, an index of maternal personality risk, encompassing aggressiveness, defendence, and low social desirability, assessed when children were 18 months old, was associated with maternal reports of child externalizing problems at age 5 (Shaw et al 1996).…”
Section: Maternal Psychological Resources and Youth Antisocial Behaviormentioning
confidence: 98%
“…For example, extensive research from both large longitudinal samples and clinical samples demonstrates links between maternal age at first birth and a diagnosis of conduct disorder, drug use, and gang membership among offspring (Nagin et al 1997;Pogarsky et al 2006;Wakschlag et al 2000). Similarly, a recent study demonstrated relatively consistent concurrent relations between maternal ratings of their trait anger and outward expression of anger and child and adolescent externalizing problems, particularly among boys (Renk et al 1999). Also, in a longitudinal study of low income children, an index of maternal personality risk, encompassing aggressiveness, defendence, and low social desirability, assessed when children were 18 months old, was associated with maternal reports of child externalizing problems at age 5 (Shaw et al 1996).…”
Section: Maternal Psychological Resources and Youth Antisocial Behaviormentioning
confidence: 98%
“…Phares and Compas (1993) demonstrated a strong link between paternal affect and children's externalizing behavior in both sexes. Recent research has concluded that sons are more directly impacted than daughters (Renk, Phares, & Epps, 1999). Renk et al (1999) analyzed 150 father-mother-adolescent triads with parental age ranging from 25 to 70 with a Mean of 42.…”
Section: Effects Of Paternal Depression Upon the Familymentioning
confidence: 99%
“…Recent research has concluded that sons are more directly impacted than daughters (Renk, Phares, & Epps, 1999). Renk et al (1999) analyzed 150 father-mother-adolescent triads with parental age ranging from 25 to 70 with a Mean of 42. Higher levels of paternal depression were related with higher levels of paternal trait anger (r = .51, p < .01), outward anger expression (r = .67, p < 0.01) as well as inward expression (r = .73, p < 0.01) (Renk et al, 1999).…”
Section: Effects Of Paternal Depression Upon the Familymentioning
confidence: 99%
“…Parental anger has been associated with poor parental adjustment (Renk et al, 1999), child behaviour problems and adjustment difficulties (Renk et al, 1999) and the use of physical punishment and coercive discipline strategies Thompson et al, 1999). In combination, a tendency towards hostile attributions and deficits in anger management may increase the risk of using excessive or severe physical punishment (Whiteman et al, 1987).…”
mentioning
confidence: 99%